(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
“Mediasia macrophylla Pimen” is both a medicinal and spice plant and is popular with the people for its a number of healing properties. The ground top of the alga is a fragrant ingredient in perfumery, a powerful appetite suppressant in medicine. Algal contains substances that have the properties of treating rheumatism, nephritis, eczema, herpes, gastrointestinal, liver and damaged areas.